The Image and the Humanities: visual poetics as the possibility of construction of knowledge - Luis Artur Costa; Tania Mara Galli da Fonseca; Margarete Axt (Educação & Realidade, 2014)
The article proposes a new perspective on the role of image in the production of knowledge, particularly with respect to the humanities. In the scientific modernity, image was regarded as an entity of imperfect ontology. Nowadays images have acquired a new importance: they have become our chief means of expression and communication, apart from their important role in research strategies. On the other hand, the production of knowledge through experimental and poetic images is still taboo in academia. Against such notion, many artists and thinkers have created a new way of conceiving the relations between images and science: the image is real and immanent to our world, since both are nothing more than action. The poetic image produces a large variety of transformations in our ways of seeing the world, resulting in an interesting research strategy.